Does childhood religiosity enhance learning motivation? Testing the role of Islamic religiosity using moderated mediation model - Sulalah (Archive for the psychology of religion, 2025)
The study assessed the role of childhood religiosity in adult religiosity and learning motivation in university participants. Participants were 338 university students (mean age = 20.42, SD = 1.53, 47% men) selected from Islamic (50%) and general universities (50%). The findings showed that participants from Islamic university compared to those from general universities scored higher on religious altruism among religiosity outcomes and on self-efficacy and active learning strategies among learning motivation outcomes. The hypothesized associations between childhood religiosity, religious altruism, religious practice, and specific learning motivation outcomes were significant. Childhood religiosity predicted two learning motivation outcomes, self-efficacy and active learning strategies, and only religious altruism in the presence of religious practice mediated these associations. In addition, university status moderated these mediated associations with stronger indirect effects for participants from Islamic universities compared to those from general universities.